Change of cytoskeleton actin isoforms spectrum in normal and modified by TGF-β1 fibroblasts at mechanical deformation - Кот, Ю. Г. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The dynamics of actin isoforms spectrum in normal deformed lung fibroblasts and fibroblasts modified by the action of TGF-β1 has been investigated. It has been shown that mechanical deformation leads to the appearance of α-actin isoform not detectable in non-deformed fibroblasts. It has been also shown that increase of α2β1 integrins on the surface of modified by TGF-β fibroblasts leads to the appearance of α-actin isoform at an earlier stage at the deformation of cells.